2009
DOI: 10.1002/ejic.200900821
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Oxygenation Studies of Carboxylate‐Bridged Diiron(II) Complexes with Aromatic Substrates Tethered to Pyridine Ligands and the Formation of a Unique Trinuclear Complex

Abstract: In this study, diiron(II) complexes were synthesized as small molecule mimics of the reduced active sites in the hydroxylase components of bacterial multicomponent monooxygenases (BMMs). Tethered aromatic substrates were introduced in the form of 2-phenoxypyridines, incorporating hydroxy and methoxy functionalities into windmill-type diiron(II) compounds [Fe2(μ-O2CArR)2-(O2CArR)2(L)2] (1–4), where –O2CArR is a sterically encumbering carboxylate, 2,6-di(4-fluorophenyl)- or 2,6-di(p-tolyl)benzoate (R = 4-FPh or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This conclusion was supported by EPR analysis of the oxygenated complexes, which showed the signal for a mononuclear Cu­(II) center and the remaining two Cu­(II) centers linked by hydroxo groups. Magnetic studies revealed a ferromagnetically coupled Cu­(II)­Cu­(II) center along with an isolated Cu­(II) in these complexes . Although these tricopper complexes do not typically support hydrocarbon oxidation, they represent a popular approach to the problem, and ligand-assisted formation of trinuclear complexes has been reported for other metal ions such as manganese, iron, cobalt, and zinc, as well. …”
Section: Toward the Development Of A Biomimetic Catalystmentioning
confidence: 86%
“…This conclusion was supported by EPR analysis of the oxygenated complexes, which showed the signal for a mononuclear Cu­(II) center and the remaining two Cu­(II) centers linked by hydroxo groups. Magnetic studies revealed a ferromagnetically coupled Cu­(II)­Cu­(II) center along with an isolated Cu­(II) in these complexes . Although these tricopper complexes do not typically support hydrocarbon oxidation, they represent a popular approach to the problem, and ligand-assisted formation of trinuclear complexes has been reported for other metal ions such as manganese, iron, cobalt, and zinc, as well. …”
Section: Toward the Development Of A Biomimetic Catalystmentioning
confidence: 86%
“…Each of the three compounds shares some structural features, particularly the Ph–O–(Zn 2 )–OOC–Ph SBU from Scheme . While this SBU is commonly seen in dimeric and polynuclear species, very few MOFs were found in the CSD (version 5.35, Nov. 2013 and updates) with this motif. {[Zn 2 (H 2 dht)(dht) 0.5 (azpy) 0.5 (H 2 O)]·4 H 2 O} (H 2 dht = dihydroxyterphthalate, azpy = 4,4′-azobipyridine) is a particular example of a fluorescent MOF with this SBU .…”
Section: Resultsmentioning
confidence: 99%
“…This fortuitous discovery that high-valent diiron terphenylcarboxylate complexes could be intercepted by tethered substrates inspired subsequent studies of the reactivity of oxygenated intermediates toward organic moieties held in close proximity to the diiron center. Attachment of benzyl [84, 85], ethyl [85], ethynyl [86], phenoxyl [87], phosphido [84, 88], or sulfido [88, 89] units to an amine or pyridine ligand afforded a series of tethered substrates that could be easily incorporated into 13 , affording the corresponding diiron(II) compounds. After exposing the substrate/diiron(II) complex to O 2 , the reaction products were analyzed by gas chromatography-mass spectrometry (GC-MS).…”
Section: Ligand Platformsmentioning
confidence: 99%